Asenapine modulates mood‐related behaviors and 5‐HT1A/7 receptors‐mediated neurotransmission. (17th April 2017) - Delcourte, Sarah; Abrial, Erika; Etiévant, Adeline; Rovera, Renaud; Arnt, Jørn; Didriksen, Michael; Haddjeri, Nasser
Summary: Aim: Asenapine is a new atypical antipsychotic prescribed for the treatment of psychosis/bipolar disorders that presents higher affinity for serotonergic than dopaminergic receptors. The objective of this study was to investigate its antidepressant‐like and antimanic‐like properties on relevant animal models of depression and mania and to assess the acute and chronic effect of Asenapine on dorsal raphe nucleus (DRN) 5‐HT cell firing activity. Methods: We assessed the effects of Asenapine using in vivo electrophysiological and behavioral assays in rats. Results: Behavioral experiments showed that Asenapine had no significant effect on immobility time in the forced swim test (FST) in control rats. In the ACTH‐treated rats, a model of antidepressant‐resistance, Asenapine failed to alter immobility time in the FST. In contrast in the sleep deprivation (SD) model of mania, acute administration of Asenapine significantly decreased the hyperlocomotion of SD rats. In the DRN, acute administration of Asenapine reduced the suppressant effect of the selective 5‐HT7 receptor agonist LP‐44 and of the prototypical 5‐HT1A receptor agonist 8‐OH‐DPAT on 5‐HT neuronal firing activity. In addition, chronic treatment with Asenapine enhanced DRN 5‐HT neuronal firing and this effect was associated with an alteration of the 5‐HT7 receptor responsiveness. Conclusion: These results confirm that Asenapine displays robust antimanic property and effective in vivo antagonistic activity at 5‐HT1A/7 receptors.